Changes in retinal metabolic profiles associated with form deprivation myopia development in guinea pigs - Jinglei Yang (Nature Portfolio, 2017)
Abstract Retinal metabolic changes have been suggested to be associated with myopia development. However, little is known about either their identity or time dependent behavior during this sight compromising process. To address these questions, gas chromatography time-of-flight mass spectrometry (GC-TOF/MS) was applied to compare guinea pig retinal metabolite levels in form deprivation (FD) eyes at 3 days and 2 weeks post FD with normal control (NC) eyes. Orthogonal partial least squares (OPLS) models discriminated between time dependent retinal metabolic profiles in the presence and absence of FD. Myopia severity was associated with more metabolic pattern differences in the FD than in the NC eyes. After 3 days of FD, 11 metabolite levels changed and after 2 weeks the number of differences increased to 16. Five metabolites continuously decreased during two weeks of FD. Two-way ANOVA of the changes identified by OPLS indicates that 15 out of the 22 metabolites differences were significant. Taken together, these results suggest that myopia progression is associated with an inverse relationship between increases in glucose accumulation and lipid level decreases in form-deprived guinea pig eyes. Such changes indicate that metabolomic studies are an informative approach to identify time dependent retinal metabolic alterations associated with this disease.